2002
DOI: 10.1007/s00441-001-0483-x
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule cold stability in supporting cells of the gerbil auditory sensory epithelium: correlation with tubulin post-translational modifications

Abstract: Sensory cells in the organ of Corti exhibit loose microtubule networks enriched in tyrosinated tubulin, whereas supporting cells have bundled microtubules containing post-translationally modified tubulin. The tubulin isoform distribution suggests that the microtubules in sensory cells are dynamic and those in supporting cells are stable. To test this, microtubule resistance to cold-induced depolymerization was examined by using immunocytochemical methods and antibodies to post-translationally modified tubulins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 82 publications
2
18
1
Order By: Relevance
“…6). Previous results have observed increases in microtubule stability upon acetylation (Bane et al, 2002;Hammond et al, 2008). Therefore, these results further the argument that post-translational modifications of microtubules might impart the stability necessary for maturing PC mechanical properties (Tolomeo and Holley, 1997).…”
Section: Cytoskeletal Architecture Mediates Developing Mechanical Prosupporting
confidence: 82%
See 2 more Smart Citations
“…6). Previous results have observed increases in microtubule stability upon acetylation (Bane et al, 2002;Hammond et al, 2008). Therefore, these results further the argument that post-translational modifications of microtubules might impart the stability necessary for maturing PC mechanical properties (Tolomeo and Holley, 1997).…”
Section: Cytoskeletal Architecture Mediates Developing Mechanical Prosupporting
confidence: 82%
“…Also, the fluorescence intensity of phalloidin increased gradually in OHCs from E16 to P5, suggesting an accumulation of actin in these cells. An antibody raised to acetylated tubulin was used to identify a subset of stable microtubules, as previous studies have shown a high correlation between microtubule stability and acetylation (Bane et al, 2002;Westermann and Weber, 2003). Immunofluorescence was found primarily in PCs and DCs in both the lumenal and basolateral surfaces of the sensory epithelium (Fig.…”
Section: Research Article Cochlear Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the majority of the microtubules in the hair cells are dynamic and free in the cytoplasm (Fig. 9Ai, iii) (Bane et al, 2002;Furness et al, 1990;Mogensen et al, 2002;Slepecky et al, 1995;Tucker et al, 1992). A distinct pattern of EB2 expression was evident in the organ of Corti with high expression of EB2 in all hair cells but very low level of expression in the supporting cells (Fig.…”
Section: Eb2 Is a Key Regulator Of Microtubule Reorganisation 4007mentioning
confidence: 99%
“…The polymodifications could specifically recruit MAPs for assembly and stabilization of the B-tubule. In vitro experiments showed that polyglutamylation is involved in the interaction between tubulin and MAPs (61,62), and a correlation between glycylation and microtubule cold stability has been established in gerbil cochlea (63), presumably involving cold MAPs (64).…”
Section: Mutations In the Tubulin Polymodification Sites Affect The Bmentioning
confidence: 99%